The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1021/acs.jproteome.8b00224
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Profiling of the Brain and Blood Metabolome in a Mouse Model of Prodromal Parkinson’s Disease Reveals Distinct Metabolic Profiles

Abstract: Parkinson's disease is the second most common neurodegenerative disease. In the vast majority of cases the origin is not genetic and the cause is not well understood, although progressive accumulation of α-synuclein aggregates appears central to the pathogenesis. Currently, treatments that slow disease progression are lacking, and there are no robust biomarkers that can facilitate the development of such treatments or act as aids in early diagnosis. Therefore, we have defined metabolomic changes in the brain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 54 publications
1
53
1
Order By: Relevance
“…Additionally, ornithine was associated with cognitive impairment and was also found in plasma metabolomics profiles in acute TBI rats (Fei et al, 2017;Wu et al, 2014). In the case of taurine and hypotaurine metabolism, the pathway enrichment analysis suggested its dysregulation in Alzheimer's disease and the development of perturbed markers in Parkinson's disease (Graham et al, 2018;Gui, Liu, Zhang, Lv, & Hu, 2015). Conversely, the results from (Menzie, Prentice, & Wu, 2013) and (Wen et al, 2018) highlighted that taurine and hypotaurine metabolism can protect neurons against inflammatory response or may be related to hypoxic preconditioning.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ornithine was associated with cognitive impairment and was also found in plasma metabolomics profiles in acute TBI rats (Fei et al, 2017;Wu et al, 2014). In the case of taurine and hypotaurine metabolism, the pathway enrichment analysis suggested its dysregulation in Alzheimer's disease and the development of perturbed markers in Parkinson's disease (Graham et al, 2018;Gui, Liu, Zhang, Lv, & Hu, 2015). Conversely, the results from (Menzie, Prentice, & Wu, 2013) and (Wen et al, 2018) highlighted that taurine and hypotaurine metabolism can protect neurons against inflammatory response or may be related to hypoxic preconditioning.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a novel approach towards the utilization of bile acids in PD is being considered. Since, to date, no reliable biomarkers of PD exist, Graham et al investigated alterations in bile acid profiles as potential biomarkers used in early diagnosis of PD [129,148]. In this respect, prodromal mouse model of PD was used to measure serum concentrations of 18 bile acids.…”
Section: Tudca In Neurodegenerative Diseasesmentioning
confidence: 99%
“…In a previous study by our group, we identified Bile Acid metabolism as one of the major biochemical pathways to be perturbed in the brain of a mouse model of prodromal PD [10]. Bile acids are molecules derived from cholesterol in hepatocytes and are used to emulsify fats in the small intestine and promote fat digestion and absorption [11,12].…”
Section: Introductionmentioning
confidence: 99%